Энергетические и размерные характеристики электроимпульсного разрушения кварцитов - Зиновьев Н. Т.; Курец В. И. Валерий Исаакович; Филатов Г. П. Геннадий Петрович; Юшков А. Ю. Анатолий Юрьевич (2011, 2011)
Заглавие с экрана